Monoclonal antibodies for the prevention of graft-versus-host disease and marrow graft rejection. The depletion of T cell subsets in vitro and in vivo. - Cobbold, S; Martin, G; Waldmann, H (1986)
One of the major complications of allogeneic bone marrow transplantation is graft-versus-host disease. This can be avoided by removing the mature T cells from the marrow, most conveniently by the use of monoclonal antibodies. However, T cell purging results in an increased tendency for the recipient to reject the donor marrow. We have developed monoclonal antibodies to L3/T4 and Lyt-2 that specifically deplete functional T cell subsets in mice. We demonstrate that such reagents can be used to control both graft-versus-host disease and marrow rejection in mouse models of bone marrow transplantation across one-haplotype or two-haplotype major histocompatibility differences. Such strategies to abrogate host resistance, by administration of anti-T-cell monoclonal antibodies to the recipient, may complement marrow T cell purging for human allogeneic bone marrow transplantation.